2021
DOI: 10.1017/ice.2021.313
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) incidence after exposures in shared patient rooms in a tertiary-care center in Iowa, July 2020–May 2021

Abstract: The incidence of COVID-19 exposures in shared patient rooms was low at our institution: 1.8/1,000 shared room patient-days. However, the secondary attack rate (21.6%) was comparable to that reported in household exposures. Lengthier exposures were associated with COVID-19 conversion. Hospitals should implement measures to decrease shared room exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…These SAR numbers are comparable to those in households (11), implying either that distancing and masking are of limited effectiveness for preventing transmission while sharing accommodations (supporting an aerosol transmission pathway between patients) (13) or that adherence to distancing and masking were low. Unsurprisingly, as also demonstrated elsewhere (8,10), the 2 parameters most strongly associated with SARS-CoV-2 were longer contact time between index and exposed patients and low Ct values (i.e., high viral loads) among index patients; Ct values <21 were shown to be associated with transmission.…”
Section: The Studymentioning
confidence: 52%
“…These SAR numbers are comparable to those in households (11), implying either that distancing and masking are of limited effectiveness for preventing transmission while sharing accommodations (supporting an aerosol transmission pathway between patients) (13) or that adherence to distancing and masking were low. Unsurprisingly, as also demonstrated elsewhere (8,10), the 2 parameters most strongly associated with SARS-CoV-2 were longer contact time between index and exposed patients and low Ct values (i.e., high viral loads) among index patients; Ct values <21 were shown to be associated with transmission.…”
Section: The Studymentioning
confidence: 52%
“…In line with our findings of SARS-CoV-2 transmission occurring through shared patient rooms, Trannel et al observed a secondary attack rate of 21.6% among patients sharing a room with a previously unidentified COVID-19 case. In their study, longer exposure was associated with a higher risk for transmission [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals are not always designed in a way to minimize the risk of patient-to-patient transmission (e.g. having limited isolation capacities) [ 4 ]. To keep medical operations running and ensure safe patient care, various IPC strategies have been developed tailored to the COVID-19 population prevalence, changes in transmissibility due to the emergence of new variants, the speed of spread, testing capacity, the availability of personal protective equipment, hospital infrastructure and vaccination coverage rates [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…44 Indeed, patients admitted to a shared hospital room with acute but occult SARS-CoV-2 infection transmit the virus to their roommate an estimated 30 to 40% of the time. 40,84,85 Indeed, one of the ironies of SARS-CoV-2 and influenza is that newly infected patients with few or no symptoms tend to be far more contagious than patients with established infections admitted for virus-associated respiratory failure. This is because viral loads tend to be highest in both SARS-CoV-2 and influenza immediately before and following symptom onset and then steadily decline thereafter.…”
Section: Symptom Screening and Universal Testingmentioning
confidence: 99%
“…44 Indeed, patients admitted to a shared hospital room with acute but occult SARS-CoV-2 infection transmit the virus to their roommate an estimated 30 to 40% of the time. 40 84 85…”
Section: Symptom Screening and Universal Testingmentioning
confidence: 99%